Response of UMR 106 cells exposed to titanium oxide and aluminum oxide nanoparticles - Di Virgilio, Ana Laura (2009)
The cytotoxicity potential of TiO2 and Al2O3 nanoparticles (NP) in UMR 106 cells was studied evaluating the lysosomal activity with neutral red uptake assay (NR), and the mitochondrial activity with tetrazolium MTT test. Different NP concentrations (10-300 microg/ml range) were used. A significant increase in the absorbance (stronger for TiO2 NP) was detected in both NR and MTT assays after 24 h exposure to the NP. However, the total cell proteins and the cell proliferation rate demonstrated that the cell viability decreased after 96 h exposure to NP. The formation of NP-containing vesicles within the cells was observed by TEM. Such event could explain the high cellular activity detected during the early stages of exposure, not related to the increase in cell viability. Results showed that the effects of NP on cell lines are dependent on the chemical composition of the particles, their concentration, exposure time and the type of treated cell. It can be concluded that the presence of TiO2 and Al2O3 NP in the cell surroundings can lead to cytotoxic effects. In the case of osteoblast cells, such events may induce osseointegration failures in orthopedic and dental implants that release NP.